Development of mobile app: Funeral Services System (FSS) / Nur Aqilah Hanapi, Nur Afiqah Syuhada Abdul Kodir and Syafnidar Abdul Halim - Hanapi, Nur Aqilah; Abdul Kodir, Nur Afiqah Syuhada; Abdul Halim, Syafnidar (Faculty of Computer and Mathematical Sciences, 2023)
The funeral services industry plays a crucial role in delivering end-of-life care and support to bereaved families during a challenging and emotionally charged period. Nonetheless, the intricacies of funeral planning and coordination often contribute to an overwhelming, confusing, and time-consuming experience, exacerbating the stress already present during this sensitive time. This underscores the necessity for a comprehensive and user-friendly platform that addresses the complexities and limitations inherent in the funeral services sector, encompassing data management and personalization of final arrangements. This project fulfills this need through the development of a mobile application named Funeral Services System (FSS), aimed at streamlining the funeral planning process for the deceased. Leveraging the Flutter platform and employing Visual Studio Code for coding purposes, the app utilizes Firebase as its database infrastructure. The successful execution of the Funeral Services System (FSS) has produced a functional platform to revolutionize the delivery of funeral services. This innovation promises families a more accessible and personalized platform for arranging their loved one's final arrangements. In charting the course for future development efforts, we propose the integration of a payment feature to enhance the overall functionality and convenience of the Funeral Services System (FSS).